Knowledge and Practice Managing of Liquid Organic Fertilizer from Waste in Tourism Village Bonjeruk, Central Lombok, West Nusa Tenggara - I Putu Dedy Arjita; Rozikin Rozikin; Dany Karmila; Sukandriani Utami; Ayu Anulus; Made Rika Anastasia Pratiwi (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Garbage is a major issue in many countries throughout the world, including Indonesia. Every year, the amount of waste produced rises in tandem with population growth. As a result, it is vital to manage liquid fertilizer made from household waste, which will aid in the reduction of community problems. The general public still has little knowledge of how liquid fertilizer is made from household garbage. This study aimed to increase community understanding and practice through training and help in the processing of household trash into liquid organic fertilizer in the tourist village of Bonjeruk, Central Lombok, West Nusa Tenggara.Subjects and Method: This was a cross-sectional study conducted in the tourist village of Bonjeruk, Central Lombok, West Nusa Tenggara, from March to December 2021. A total of 27 subjects were selected in this study. The variables in this study were knowledge and behavior. The training in management household waste into organic liquid fertilizer was carried out for 4 months. The stages of intervention were as follows: 1) Education and simulation of sorting organic and non-organic waste; 2) Separating vegetable and fruit waste from rice, meat, and bone residue. Vegetable and fruit waste was transferred into composer barrels; 3) Spraying diluted bio-activator every time they enter organic waste; 4) Filling cans continuously with garbage; 5) Every 14th day, the liquid fertilizer can be harvested; 6) Liquid fertilizer can be used after being left for 14 days outside the composer barrel by dilution. The data were collected by questionnaire and analyzed descriptively.Results: After 4 months of training, the community was able to process liquid fertilizer from the use of compost barrel and natural bio-activators from household waste. Community knowledge related to liquid fertilizer after training (Mean= 91.48; SD= 11.12) was higher than before training (Mean= 85.56; SD= 12.57). Household waste management practice after training (Mean= 94.07; SD= 11.94) was better than before training (Mean= 45.93; SD= 22.32).Conclusion: Community knowledge and practice increase after going through training in processing household waste into liquid organic fertilizer in the tourist village of Bonjeruk, Central Lombok, West Nusa Tenggara.Keywords: organic liquid fertilizer, tourist village, household waste. Correspondence:Rozikin. Faculty of Medicine, Universitas Islam Al-Azhar. Jl. Unizar No.20, Turida, Kec. Sandubaya (83232), Kota Mataram, West Nusa Tenggara. Email: rozikin@mail.ugm.ac.id. Mobile: +62 878-2000-7449.Journal of Health Promotion and Behavior (2022), 07(04): 335-339DOI: https://doi.org/10.26911/thejhpb.2022.07.04.06